Controlled, Constrained, or Flexible? How Self-Management Goals Are Shaped By Patient–Provider Interactions. (March 2019) - Franklin, Marika; Lewis, Sophie; Willis, Karen; Rogers, Anne; Venville, Annie; Smith, Lorraine
A person-centered approach to goal-setting, involving collaboration between patients and health professionals, is advocated in policy to support self-management. However, this is difficult to achieve in practice, reducing the potential effectiveness of self-management support. Drawing on observations of consultations between patients and health professionals, we examined how goal-setting is shaped in patient–provider interactions. Analysis revealed three distinct interactional styles. In controlled interactions, health professionals determine patients' goals based on biomedical reference points and present these goals as something patients should do. In constrained interactions, patients are invited to present goals, yet health professionals' language and questions orientate goals toward biomedical issues. In flexible interactions, patients and professionals both contribute to goal-setting, as health professionals use less directive language, create openings, and allow patients to decide on their goals. Findings suggest that interactional style of health professionals could be the focus of interventions when aiming to increase the effectiveness of goal-setting.